KEMAMPUAN MENENTUKAN PEMAKAIAN HURUF KAPITAL DAN HURUF MIRING SISWA SMP ANNUR PEKANBARU - Alya Surya Novriani; Mangatur Sinaga; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe and explain the level of ability of Annur Pekanbaru Middle School students in determining the use of capital letters and italics. This research uses descriptive method using objective text data of Annur Pekanbaru Middle School students. This descriptive method uses quantitative research in its use. Because this study contains measurements of the level of students' ability to determine capital letters and italics, this study uses quantitative research. In examining the level of ability of Annur Pekanbaru Middle School students in the use of capital letters and italics we must calculate the scores of Annur Pekanbaru Junior High School students. From there then we can find out how much the ability of Annur Pekanbaru junior high school students to determine the use of capital letters and italics. The results showed that: (1) the average percentage in the ability to determine the use of capital letters of Annur Junior High School students in Pekanbaru was 78.49. The percentage is included in the medium category, (2) the average percentage in the ability to determine the use of italics is 76.34. These percentages fall into the medium category.Key Words: Ability, Capital Letters, Italics